2015
DOI: 10.5935/1678-9741.20150028
|View full text |Cite
|
Sign up to set email alerts
|

Surgery of the aortic root: Should we go for the valve-sparing root reconstruction or the composite graft-valve replacement is still the first choice of treatment for these patients?

Abstract: ObjectiveTo compare the results of the root reconstruction with the aortic valve-sparing operation versus composite graftvalve replacement.MethodsFrom January 2002 to October 2013, 324 patients underwent aortic root reconstruction. They were 263 composite graft-valve replacement and 61 aortic valve-sparing operation (43 reimplantation and 18 remodeling). Twenty-six percent of the patients were NYHA functional class III and IV; 9.6% had Marfan syndrome, and 12% had bicuspid aortic valve. There was a predominanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Valve sparing aortic root replacement (VSRR) surgery is one of the key methods of intervention for the treatment of pathologies affecting the aortic root and the aortic valve (AV). 1 Pathologies such as connective tissues defects seen in Marfan syndrome; secondary atherosclerotic degeneration; congenital anomalies within the AV; acute infective endocarditis; and rheumatic heart disease can all lead to life-threatening sequelae such as progressive aortic dilatation and can later progress to severe aortic regurgitation which often requires immediate surgical intervention. 2 It was in the early 1990s that two mainstay techniques came into practice 3 ; David's valve-sparing aortic root reimplantation 4…”
Section: Introductionmentioning
confidence: 99%
“…Valve sparing aortic root replacement (VSRR) surgery is one of the key methods of intervention for the treatment of pathologies affecting the aortic root and the aortic valve (AV). 1 Pathologies such as connective tissues defects seen in Marfan syndrome; secondary atherosclerotic degeneration; congenital anomalies within the AV; acute infective endocarditis; and rheumatic heart disease can all lead to life-threatening sequelae such as progressive aortic dilatation and can later progress to severe aortic regurgitation which often requires immediate surgical intervention. 2 It was in the early 1990s that two mainstay techniques came into practice 3 ; David's valve-sparing aortic root reimplantation 4…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, they noticed that bleeding (requiring re-exploration) was lower in the valve-sparing group and they associated the higher mortality rate in the composite valve graft group with early and late-term complications related to bleeding. Additionally, there were significant differences between the groups in terms of thromboembolic events in that study 9…”
Section: Discussionmentioning
confidence: 69%
“…In a recent study, Lamana et al9 analysed 324 patients, of whom 263 had undergone mechanical composite valve graft surgery and 61 valve-sparing root surgery. They observed that there were no statistically significant differences in short-term mortality rates (p = 0.71), but the long-term mortality rate was lower in the valve-sparing group (p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…However, no difference was found in terms of ventricular function and LV end-diastolic volume between these techniques. The mortality rate of patients with mechanical valve was found to be higher at the 10-year follow-up period, although there was no difference in mortality in their 5-year follow-up [26,29] .…”
Section: Discussionmentioning
confidence: 83%